Chitosan extraction from Amanita phalloides: yield, crystallinity, degree of deacetylation, azo dye removal and antibacterial properties - Hemmami, Hadia; Ben Amor, Ilham; Zeghoud, Soumeia; Ben Amor, Asma; Laouini, Salah Eddine; Alsalme, Ali; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
Chitosan, a biopolymer obtained from chitin, is known for its remarkable adsorption abilities for dyes, drugs, and fats, and its diverse array of antibacterial characteristics. This study explores the extraction and characterization of chitosan from the mycelium of Amanita phalloides. The moisture content, ash content, water binding capacity, fat binding capacity, and degree of deacetylation of the extracted chitosan were determined. The chitosan exhibited a high yield of 70%, crystallinity of 49.07%, a degree of deacetylation of 86%, and potent antimicrobial properties against both Gram-negative and Gram-positive bacteria. The study also examined the adsorption capabilities of chitosan to remove methylene blue (MB) dye by analysing specific factors like pH, reaction time, and MB concentration using the response surface model. The highest degree of MB dye removal was 91.6% at a pH of 6, a reaction time of around 60 min and an initial dye concentration of 16 ppm. This experimental design can be applied for chitosan adsorption of other organic compounds such as dyes, proteins, drugs, and fats.